Adaptive backstepping control of an induction motor under time-varying load torque and rotor resistance uncertainty. (3rd February 2009) - Ebrahim, Arbin; Murphy, Gregory
A new global adaptive controller is designed for induction motor speed control based on measurements of speed and stator current. The designed partial state feedback controller is singularity free, and guarantees asymptotic tracking of smooth reference trajectories for the speed of the motor under time-varying load torque and rotor resistance uncertainty, for any initial condition. The new control algorithm generates estimates for unknown time-varying load torque, rotor resistance and unmeasured state variables (rotor fluxes) which asymptotically tracks and converges to their true values. The rotor flux modulus asymptotically tracks a desired reference signal which allows the motor to operate within its specifications. The control strategy yields decoupled rotor speed and rotor flux amplitude tracking control goals which allows the selection of an appropriate flux modulus for the rotor to maximise efficiency.